Interfacial pH measurements during CO2 reduction on gold using a rotating ring-disk electrode. Issue 4 (12th January 2023) - Liu, Xuan; Monteiro, Mariana C. O.; Koper, Marc T. M.
Abstract : Variation of interfacial pH during CO2 reduction reaction in near-neutral media is monitored by a functionalised RRDE pH sensor. CO2 is exhausted near the interface when reaching high interfacial alkalinity at negative potential. Abstract : Insights into how to control the activity and selectivity of the electrochemical CO2 reduction reaction are still limited because of insufficient knowledge of the reaction mechanism and kinetics, which is partially due to the lack of information on the interfacial pH, an important parameter for proton-coupled reactions like CO2 reduction. Here, we used a reliable and sensitive pH sensor combined with the rotating ring-disk electrode technique, in which a functionalized Au ring electrode works as a real-time detector of the OH − generated during the CO2 reduction reaction at a gold disk electrode. Variations of the interfacial pH due to both electrochemical and homogeneous reactions are mapped and the correlation of the interfacial pH with these reactions is inferred. The interfacial pH near the disk electrode increases from 7 to 12 with increasing current density, with a sharp increase at around −0.5 V vs. RHE, which indicates a change of the dominant buffering species. Through scan rate-dependent voltammetry and chronopotentiometry experiments, the homogenous reactions are shown to reach equilibrium within the time scale of the pH measurements, so that the interfacial concentrations of different carbonaceous species can be calculated using equilibrium constants. Furthermore, pH measurements were also performed under different conditions to disentangle the relationship between the interfacial pH and other electrolyte effects. The buffer effect of alkali metal cations is confirmed, showing that weakly hydrated cations lead to less pronounced pH gradients. Finally, we probe to which extent increasing mass transport and the electrolyte buffer capacity can aid in suppressing the increase of the interfacial pH, showing that the buffer capacity is the dominant factor in suppressing interfacial pH variations.